Safety and Efficacy of an Intravaginal Prebiotic Gel in the Prevention of Recurrent Bacterial Vaginosis: A Randomized Double-Blind Study - Isabelle Coste; Philippe Judlin; Jean-Pierre Lepargneur; Sami Bou-Antoun (Obstetrics and Gynecology International)
Objective. This study was performed to evaluate the efficacy and safety of a prebiotic treatment in the balance recovery of the vaginal flora in subjects previously treated for bacterial vaginosis (BV). Study Design. A randomized trial was carried out on 42 subjects with an active prebiotic group compared to a placebo group. The main evaluation criterion was the quantification of the vaginal flora measured by the Nugent score. Secondary criteria included vaginal pH and BV recurrence. Results. After 8 days of treatment, all subjects who received the prebiotic had a normal Nugent score, whereas 33% of the subjects treated with placebo had an intermediate or positive Nugent score. After 16 days of application, a normal Nugent score was maintained in all subjects treated with the prebiotic, whereas in the placebo group 24% of the subjects still had an elevated Nugent score. Moreover, the maintenance of (or reversion to) a normal flora was associated with the maintenance of (or reversion to) physiological pH values. Conclusions. The intravaginal gel treatment improves the recovery of a normal vaginal flora after the treatment of a BV episode, which should warrant a reduction in the risk of further recurrences.